2006
DOI: 10.1001/archinte.166.20.2278
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits in Patients With Antiphospholipid Syndrome

Abstract: Cognitive deficits may often be found among patients with APS, independent of any history of central nervous system involvement. Livedo reticularis and the presence of white matter lesions on brain magnetic resonance imaging are associated with an increased risk for cognitive dysfunction in APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…Although scant, studies in primary APS have reported a high predominance of cognitive deficits involving attention and verbal fluency [12,13]. In addition, several authors reported the occurrence of chronic or recurrent ischemic events affecting small or large cerebral vessels and leading to multi-infarct dementia [1].…”
Section: The Current Clinical Spectrum Of Anti-phospholipid Syndromementioning
confidence: 99%
“…Although scant, studies in primary APS have reported a high predominance of cognitive deficits involving attention and verbal fluency [12,13]. In addition, several authors reported the occurrence of chronic or recurrent ischemic events affecting small or large cerebral vessels and leading to multi-infarct dementia [1].…”
Section: The Current Clinical Spectrum Of Anti-phospholipid Syndromementioning
confidence: 99%
“…White matter disease is a marker of small vessel disease and increases with aging and cumulative burden of cerebrovascular risk factors(12, 18). Additionally, chronic inflammatory diseases such as lupus erythematous may trigger white matter disease without these cerebrovascular risk factors(29, 30). …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies’ limitations may be addressed by research using brain tissue with definitive identification of infarcts, including microscopic infarcts, which elude identification by currently available neuroimaging technology [12, 22]. Case reports with brain tissue data showed perivascular inflammation and amyloid-β deposition in vessels, while others found changes suggestive of a non-inflammatory vasculopathy [23].…”
Section: Discussionmentioning
confidence: 99%